2021
DOI: 10.1111/obr.13294
|View full text |Cite
|
Sign up to set email alerts
|

Bariatric surgery and the liver—Mechanisms, benefits, and risks

Abstract: The prevalence of obesity and metabolic diseases such as type 2 diabetes and nonalcoholic fatty liver disease (NAFLD) has risen dramatically over the past decades.At present, bariatric surgery is the most effective treatment for this global health problem, through effects on food intake, gut hormone secretion, metabolic signaling pathways, and adipose tissue dysfunction. The liver occupies a central role in carbohydrate, protein, and lipid metabolism. Notably, a reduction in hepatic fat content and an improvem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 137 publications
(272 reference statements)
1
31
0
Order By: Relevance
“…The mechanisms of BMS and improved liver health are not yet fully elucidated. Potential mechanisms include an increase in gut hormone signaling such as GLP-1, remission of hepatic and adipose tissue inflammation, lipid malabsorption, and augmentation of enterohepatic bile acid secretion and signaling [ 173 , 174 ]. BMS decreases food intake and adiposity [ 157 , 175 ], which are independent predictors of onset and progression of NAFLD/NASH to HCC [ 15 ].…”
Section: Treatment Strategies For Obesity and Their Association With ...mentioning
confidence: 99%
“…The mechanisms of BMS and improved liver health are not yet fully elucidated. Potential mechanisms include an increase in gut hormone signaling such as GLP-1, remission of hepatic and adipose tissue inflammation, lipid malabsorption, and augmentation of enterohepatic bile acid secretion and signaling [ 173 , 174 ]. BMS decreases food intake and adiposity [ 157 , 175 ], which are independent predictors of onset and progression of NAFLD/NASH to HCC [ 15 ].…”
Section: Treatment Strategies For Obesity and Their Association With ...mentioning
confidence: 99%
“…By comparing the obtained results to transcriptomics datasets of liver samples from NAFLD patients after bariatric surgery, we aimed at gaining insights in the mechanisms that could possibly lay at the basis of the negative outcome of the interim analysis of the phase 3 ‘RESOLVE-IT’ trial. Bariatric surgery impacts several hepatic metabolic pathways even before weight loss occurs, leading to a reduction of liver triglyceride levels as a major cause for the reduction of NASH [ 10 , 11 ]. Therefore, it was considered as a valid reference.…”
Section: Introductionmentioning
confidence: 99%
“…Adipose tissue, liver tissue and skeletal muscle are important metabolic tissues that play important roles in the progression of insulin resistance and obesity [ 6 ]. Previous studies reported that hypertrophy, inflammatory response and adipokine dysregulation of adipose tissue may affect the outcomes of BS [ 7 ] and suggested that BS could reduce hepatic fat contents and improve hepatic insulin resistance [ 8 ]. In addition, Peter H Albers et al demonstrated that the improved molecular insulin-sensitive phenotype of skeletal muscle and adipose tissue contributed to the improved whole body insulin action and substantial weight loss after BS [ 9 ].…”
Section: Introductionmentioning
confidence: 99%